Peers' Choices Influence Adolescent Risk‐taking Especially When Explicit Risk Information is Lacking. (6th March 2021) - Osmont, Anaïs; Camarda, Anaëlle; Habib, Marianne; Cassotti, Mathieu
Abstract : This study examines the impact of peers' previous cautious versus risky choices on adolescents' risk‐taking depending on the level of information about the risk. Adolescents completed an adaptation of the BART that manipulated social influence (cautious and risky) and risk information (i.e., informed, noninformed). Results showed that social influence impacts adolescents' decisions on the noninformed BART but not on the informed BART. In the noninformed BART, the peers' cautious choices strongly decreased risk‐taking and led to greater performance. The peers' risky choices increase adolescents' risk‐taking, but this effect is limited to situations involving minimal risk. Thus social experience may be a specific social context that represents a valuable source of information during adolescence, especially in situations with high uncertainty.